"Like Poles Repel While Unlike Poles Attract": Contextual Performance Effects of Supply Base R & D, Focal Firm R & D, and Commercialization. (19th March 2019) - Pathak, Surya; Sen, Pradyot K.; Jayaram, Jayanth; Miller, James M.
ABSTRACT: We show that the ability of a firm to enhance its performance through R & D and commercialization efforts is dependent on the alignment of R & D intensity of the firm's supply base with its own R & D intensity. We employ a multi‐industry dataset consisting of 163 focal firms and their supply bases, spanning the years 1976 to 2009. Focal firms that have higher R & D expenditure compared to their industry average, enjoy greater performance benefits from their own R & D and commercialization efforts, as compared to when they have a Low R & D‐intense supply base. On the other hand, focal firms with lower R & D expenditure compared to their industry average, benefit more from their own R & D and commercialization expenditure when they have a High R & D supply base. When levels of R & D expenditure are matched with respect to the supply base (Low–Low or High–High), focal firms tend to derive less marginal performance benefits from their own R & D and commercialization expenditures. This pattern of results constitutes a "polarity effects" phenomenon, i.e., unlike poles attract. Further, for the High R & D focal firm–Low R & D supply base combination (and vice versa), we show that although both R & D and commercialization efforts have a separate and positive effect on the focal firm's financial performance; taken together, they have a negative synergy. Through a response surface analysis, we are able to show that there is a commercialization threshold, below which the Low R & D focal firm–High R & D supply base derives lower total benefits as compared to a High R & D focal firm–Low R & D supply base combination.